KEBIJAKAN PIDANA KEKERASAN SEKSUAL YANG DILAKUKAN KEPADA LEBIH DARI SATU ORANG ANAK DALAM PERSPEKTIF KEADILAN, KEPASTIAN HUKUM DAN KEMANFAATAN - Aprivella, Erika; Wahid, Eriyantouw (Universitas Trisakti, 2024)
The research discusses sexual violence, which is an act committed by a defendant who forces children to engage in sexual intercourse, resulting in 13 child victims, some of whom have given birth. This is based on case study Number 989/Pid.Sus/2021/PN.Bdg. The issues addressed are: 1) What are the criminal policies regarding sexual violence (intercourse) committed against more than one child? 2) How does the ruling of Judge Number 989/Pid.Sus/2021/PN.Bdg. reflect justice, legal certainty, and utility in cases of sexual violence (intercourse) against multiple children? The research employs a juridical-normative legal study method, is descriptive-analytical in nature, and utilizes both secondary and primary data. Data is collected through literature reviews and analyzed qualitatively. Conclusions are drawn using deductive logic. The answers to the problems are: 1) The criminal legal policy is an effort to combat crime and is an integral part of community protection efforts. The legal policies include: Law Number 23 of 2002 on Child Protection, Law Number 35 of 2014 amending Law Number 23 of 2002 on Child Protection, Law Number 17 of 2016 concerning the Establishment of Government Regulation in Lieu of Law Number 1 of 2016 on the Second Amendment to Law Number 23 of 2002 on Child Protection into Law, and Law Number 12 of 2022 on Sexual Violence Crimes. 2)The handling of the case in this instance does not reflect the principle of justice, as the death penalty was imposed despite the Constitutional Court Decision No. 2-3/PUU-V/2007 and the Criminal Code of 2023 stating that the death penalty can be executed with a 10-year probationary period. This period allows for the possibility of change in the Defendant, showing remorse or developing a good character, which could lead to the death penalty being commuted to a life sentence or a 20-year term, with eligibility for remission and conditional sentences.